Invasive Group A Streptococcal Infections: Benefit of Clindamycin, Intravenous Immunoglobulins and Secondary Prophylaxis - Laho, Delphine; Blumental, Sophie; Botteaux, Anne; Smeesters, Pierre R. (Frontiers in Pediatrics, 2021)
Introduction Mortality associated with invasive group A streptococcal infections (iGAS) remains high especially among adults, with lower mortality in children. The added value of both clindamycin and immunoglobulins in such treatment is still controversial, as is the need for antibiotic secondary prophylaxis. It is unlikely that conclusive randomized clinical studies will ever definitively end these controversies. Materials and methods: A clinical and experimental literature review was conducted in Pubmed, Cochrane and lay literature to determine the benefit of adding clindamycin and immunoglobulins to β-lactams in the management of iGAS, as well as the need for secondary prophylaxis measures in close contacts. Results: This review includes 2 meta-analyses, 2 randomized controlled trials, 4 prospective studies, 5 retrospective studies and microbiological studies. To reduce mortality and morbidity, it appears useful to add clindamycin to β-lactams in severe clinical presentation including necrotizing fasciitis or streptococcal toxic shock syndrome and immunoglobulins for the latter two presentations. The high risk of secondary infection in household contacts justifies taking preventive measures. Conclusions: Both clinical studies and available experimental evidence suggest that adding clindamycin and immunoglobulins as adjunctive therapies in the management of invasive group A streptococcal infections may reduce mortality. Household contacts should be warned about the increased risk of secondary infection and chemoprophylaxis may be considered in certain situations.